Public Policy in Managing Modern Stores for Community Development - Suroso, Suroso (Jurnal Bina Praja: Journal of Home Affairs Governance, 2016)
Modern stores have grown rapidly in Pati Regency but some of them are out of control, such as too near traditional markets. The objective of the research is to analyse the existence of modern stores, the distribution of them, the local government regulation of them, and to analyse advantages and disadvantages of them for community development. This research uses descriptive quantitative approach. Data collecting is conducted by observation, interview, and field events. This research uses descriptive analysis. There are five main findings in the research. Firstly, modern stores in the study area have grown rapidly. Secondly, the distribution of modern stores is not well managed, in which 19 out of 53 modern stores (35.84%) are established in the sites near traditional markets. Thirdly, the existence of modern stores is not well controlled because 9 out of 53 modern stores are in problems with their permits. Fourthly, there are 20 modern stores which have roles in community development by providing retail space for informal traders. Fifthly, the local government policy concerning minimarket is not well formulated being not governed the distance between modern store to the pre-existing traditional markets and being to conduct a moratorium of permit serving for the establishment of modern stores, which does not refer to national law. Therefore, the existing local policy in managing modern stores should be reviewed to support community development.